The impact of price transparency of bundled vacation packages on travel decision making: An experimental study - Bai, Shizhen; Chu, Lingyun; Fam, Kim-Shyan; Wei, Sheng (Frontiers in Psychology, 2022)
Price transparency is a vital factor in consumers’ judgements and decisions. When selecting a bundled vacation package, travelers are often influenced by transparency in the prices of individual elements of the package. However, because of the diversity of elements bundled in a vacation package, it is a challenge to research the impact of price transparency. To try to overcome this challenge, our study used five experiments to examine the primary impact of element price transparency on travelers’ purchases, along with the moderating effects of consumer involvement and the vertical position of element prices in product descriptions. For the primary effect, we found that tourists preferred vacation packages with low transparency in element prices. We also found that the primary effect of price transparency remained consistent and robust across both revised and actual vacation packages. For moderating effects, we found that tourists with low involvement attached greater importance to price transparency than those with high involvement when the element price was presented higher in the product description of the travel package. The findings of the five experiments have implications for future research and practical implications for tourism professionals designing and marketing vacation packages.